(untitled) (Società e diritti, 2020)
The autor, after having described the ideolagical and cultural issues linked to the diffucult implementation of Faro Convention in the Italian legal framework, analyses its innovative contents. The Faro Convention contents are described as a new approach to cultural heritage, from a right of the cultural heritage to a right to cultural heritage, with a different attention to people, communities and cultural rights more in general.